Ethical Digital Marketing and Consumer Loyalty Among Millennials and Generation Z: A Bibliometric Analysis and Systematic Literature Review - Akh Lutfi Akh; Pribanus Wantara; A. Yahya Surya Winata (Amkop Management Accounting Review (AMAR), 2026)
The rapid development of digital technology has transformed the way companies interact with consumers, making ethical considerations in digital marketing increasingly important. Millennials and Generation Z are characterized by high digital literacy and greater sensitivity toward transparency, data privacy, and corporate sustainability commitments. However, studies on ethical digital marketing, brand trust, and consumer loyalty remain fragmented and lack an integrated conceptual framework. This study aims to map the development of the literature, identify dominant research themes, and synthesize research gaps related to the relationship between ethical digital marketing, brand trust, and consumer loyalty among Millennials and Generation Z. A Systematic Literature Review (SLR) approach based on the PRISMA framework was employed to analyze international scientific articles . The findings reveal three dominant themes in the literature: transparency and brand trust, sustainability marketing and green trust, and data ethics and digital privacy. The results further indicate that brand trust serves as the primary mechanism linking ethical digital marketing practices to consumer loyalty. In addition, the review identifies a lack of studies integrating multiple dimensions of ethical digital marketing into a comprehensive conceptual model, particularly in the context of Millennials and Generation Z.